Wild Focus : Twenty-five Years of Texas Parks & Wildlife Photography - Nottingham, Earl; Saldaña, Lydia; Smith, Carter P. (Book collections on Project MUSE., 2022)
"In Wild Focus, Earl Nottingham, chief photographer for the Texas Parks & Wildlife Department and its magazine, provides a unique perspective on Texas featuring images of the woods, waters, and wildlife of the Lone Star landscape. Nottingham's engaging photography-landscape, nature, and wildlife; environmental portraiture of people; photojournalistic coverage of events, including natural disasters-provides a cohesive overview of biodiversity and the state of conservation in Texas. The nearly 200 stunning photographs collected here encompass the expansive mission of TPWD, presenting traditional landscape images from state and national parks as well as from vast private lands. Cultural and historic sites are included along with environmental portraits of the people associated with those sites. From the state's wildlife, both great and small, to nature shown in not only its beauty but also its fury-wildfires, hurricanes, and floods-Earl Nottingham offers a visual compendium of events, people, places, and things that have shaped the face of natural Texas. The author logged untold miles and wore through many sets of tires to offer timely stories that would "inform, educate, entertain, and empower" readers about the outdoors. These images that capture the richness and diversity of wild Texas inspire a greater appreciation for the state's beauty and promote a sense of stewardship for its natural treasures"--